Quality of Life in Patients with Nasal Obstruction after Septoplasty: A Single Institution Prospective Observational Study - Dąbrowska-Bień,Justyna (2021)
Abstract Introduction Nasal obstruction is a common symptom in otorhinolaryngological practice. It can impact significantly on the quality of life of the individual. Objective The primary goal of the present study was to evaluate quality of life after septoplasty in adults with nasal obstruction. A secondary goal was to assess the effectiveness of septoplasty. Methods This was a single institution prospective observational study. Patients had experienced septal deviation and symptomatic nasal obstruction with no benefit from medical treatment. There were 51 patients who completed the Nasal Obstruction Symptom Evaluation (NOSE-POL) scale as well as theVisual Analogue Scale (VAS) before undergoing septoplasty, 3 months later, and finally 7 months after surgery. Patients evaluated changes in their nasal obstruction and changes in their quality of life using the Clinical Global Impression Scale (CGI-S). Results There was a significant improvement in nasal obstruction after septoplasty. Before septoplasty, the mean score on NOSE was 60.3 ± 20.4; 3 months after surgery, it was 32.9 ± 16.8; and 7 months after surgery it was 39.6 ± 33.2. The VAS results also proved a significant enhancement in nasal obstruction after septoplasty. Patients reported an improvement in nasal obstruction as well as a positive change in quality of life, confirming the effectiveness of septoplasty. Conclusions In patients with deformed septum, septoplasty contributes to high satisfaction of the patient and a compelling improvement in disease-specific quality of life. The NOSE-POL questionnaire is a useful tool for measuring the outcomes of this procedure.